Comprehensive medication management services influence medication adherence among Japanese older people - Hirakawa, Yoshihisa (J Rural Med, 2015)
Objective: Assistance from health professionals is very important to ensure medication adherence among older people. The present study aimed to assess the relationship between receipt of comprehensive medication management services by primary care physicians and medication adherence among community-dwelling older people in rural Japan. Methods: Data including medication adherence and whether or not a doctor knew all the kinds of medicines being taken were obtained from individuals aged 65 years or older who underwent an annual health checkup between February 2013 and March 2014 at a public clinic in Asakura. The subjects were divided into 2 groups: adherent (always) and non-adherent (not always). A logistic regression analysis was performed to assess the association between the presence of a doctor who was fully responsible for medication adherence and self-reported adherence. Predictors that exhibited significant association (p-value < 0.05) with medication adherence in a univariate analysis were entered in the model as possible confounding factors. The results were presented as odds ratios (OR) and 95% confidence intervals (CI). Results: Among four-hundred ninety-seven subjects in total, the adherent group included 430 subjects (86.5%), and its members were older than those of the non-adherent group. Significant predictors of good medication adherence included older age, no discomforting symptoms, eating regularly, diabetes mellitus and having a doctor who knew all the kinds of medicines being taken. After being adjusted for confounding variables, the subjects with a doctor who knew all the kinds of medicines they were taking were three times more likely to be adherent to medication (OR 3.01, 95% CI 1.44-6.99). Conclusion: Receipt of comprehensive medication management services for older people was associated with medication adherence.